Enhancing Surface Roughness in the Taguchi Method for Turning Alloy Steel in Wet and Dry Environments - Rone (International Journal of Robotics and Automation in Mechanics, 2025)
The present investigation focuses on evaluating the performance of turning operations in alloy steel with particular emphasis on the effect of cutting parameters on surface roughness. In the machining of alloy steel, tool life and surface integrity are significantly influenced by parameters such as spindle speed, depth of cut, and feed rate. Among these, feed rate has been observed to exert the most prominent effect on surface roughness. To systematically analyze these influences, the Taguchi method employing an L9 orthogonal array design was selected as the most suitable approach for experimental planning. This method not only reduces the number of experimental trials but also provides an efficient statistical framework to evaluate the contribution of individual parameters. Three levels were chosen for each cutting factor to comprehensively study their interactions and effects. The experiments were performed under both wet and dry turning conditions using a CNC lathe machine, with workpieces of 45 mm diameter and 145 mm length. For each condition, three sets of trials were conducted to ensure repeatability, and the average values were considered as the final outcomes. The signal-to-noise (S/N) ratio analysis was used to determine the robustness of the parameters, while analysis of variance (ANOVA) was employed to quantify the percentage contribution of each factor. Optimization of the experimental data was carried out using Minitab 17 software, which assisted in identifying the optimal combination of parameters for achieving minimum surface roughness. The results revealed that feed rate was the most critical factor influencing surface finish, followed by spindle speed and depth of cut. Furthermore, it was observed that wet turning yielded comparatively better results in terms of surface quality when compared to dry turning, thereby highlighting the importance of lubrication in improving machining performance. The findings of this work provide useful insights for industry practitioners to optimize cutting conditions, enhance tool life, and improve productivity in alloy steel machining. This study demonstrates the efficiency of the Taguchi method in machining optimization and emphasizes its applicability in both academic and industrial research contexts.
Keywords: Orthogonal Array; Taguchi method; roughness; signal-to-noise; spindle; turning